MICRO-FRAGMENTED ADIPOSE TISSUE IN THE KNEE OSTEOARTHRITIS UNDER LOCAL ANESTHESIA - Bruno Butturi Varone; Henrique Fuller; Daniel Perini; Daniel Peixoto Leal; Riccardo Gomes Gobbi; Marco Kawamura Demange (Acta Ortopédica Brasileira)
Abstract Objective: To assess the feasibility of the entire micro fragmented adipose tissue knee injection procedure under local anesthesia. From the subcutaneous harvesting and microfragmentation process to the intrarticular knee injection. Methods: A patient with bilateral knee osteoarthritis underwent adipose tissue harvesting and bilateral intra-articular micro fragmented adipose tissue knee injection under local anesthesia. Patient-related outcomes were collected before the procedure, 12 months, and 24 months follow-up. Womac, Koos, and VAS were recorded. Results: The visual analog scale, KOOS questionnaire, and WOMAC score all improved in the 12- and 24-month follow-ups. Conclusion: Adipose tissue harvesting and micro fragmented adipose tissue knee injection are procedures that can be performed under local anesthesia and have good patient report outcomes. Level of Evidence IV; Therapeutic Study.